2020
DOI: 10.1200/jco.19.02767
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Avoidance During Whole-Brain Radiotherapy Plus Memantine for Patients With Brain Metastases: Phase III Trial NRG Oncology CC001

Abstract: PURPOSE Radiation dose to the neuroregenerative zone of the hippocampus has been found to be associated with cognitive toxicity. Hippocampal avoidance (HA) using intensity-modulated radiotherapy during whole-brain radiotherapy (WBRT) is hypothesized to preserve cognition. METHODS This phase III trial enrolled adult patients with brain metastases to HA-WBRT plus memantine or WBRT plus memantine. The primary end point was time to cognitive function failure, defined as decline using the reliable change index on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
410
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 572 publications
(464 citation statements)
references
References 37 publications
5
410
2
4
Order By: Relevance
“…Radiation damage to the hippocampus is a key factor leading to cognitive decline [11]. The NRG-CC001 trial [12] reported that WBRT with hippocampal sparing could decrease neurocognitive toxicity compared with traditional WBRT. As the incidence of BMs within 5 mm around the hippocampus is only 4.7 to 8.6% [13][14][15], the limitation of the radiotherapy dose in the hippocampal area can decrease the neurocognitive toxicity related to WBRT without decreasing the intracranial tumor control rate [16].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation damage to the hippocampus is a key factor leading to cognitive decline [11]. The NRG-CC001 trial [12] reported that WBRT with hippocampal sparing could decrease neurocognitive toxicity compared with traditional WBRT. As the incidence of BMs within 5 mm around the hippocampus is only 4.7 to 8.6% [13][14][15], the limitation of the radiotherapy dose in the hippocampal area can decrease the neurocognitive toxicity related to WBRT without decreasing the intracranial tumor control rate [16].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of measures have been attempted to minimize the radiation dose to the hippocampus in clinical trials. A phase III clinical trial (NRG Oncology CC001, NCT02360215) showed that combined treatment with hippocampal avoidance whole-brain radiotherapy (HA-WBRT) and memantine was better than combined treatment with WBRT plus memantine in preserving cognitive function and patient-reported symptoms in patients with brain metastases [45]. The second ongoing phase III trial, NRG Oncology-CC003 (NCT02635009), is assessing the effects of WBRT with or without HA-WBRT in treating patients with limited-stage or extensive-stage small-cell lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at least at one time point with significantly better results regarding executive function, processing speed, and delayed recognition was found in the memantine group. In a recently published phase III trial of 518 patients receiving whole-brain irradiation, hippocampus-sparing and memantine were combined and compared to memantine without sparing of the hippocampi [11]. The combined approach resulted in better preservation of cognitive function without impairing cerebral progression-free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In patients expected to have longer survival times, outcomes can be improved with doses > 30 Gy [8]. Moreover, the modern approaches of hippocampus-sparing and addition of memantine can significantly reduce neurocognitive decline, an important late toxicity of whole-brain-irradiation [9][10][11]. The risk of experiencing this late toxicity increases with time, and therefore, gains importance in longer-term survivors.…”
Section: Introductionmentioning
confidence: 99%